Zinc‐finger E‐box‐binding homeobox 1 (ZEB1) plays a crucial role in the maintenance of lung cancer stem cells resistant to gefitinib. Issue 10 (25th March 2021) - Nurwidya, Fariz; Takahashi, Fumiyuki; Winardi, Wira; Tajima, Ken; Mitsuishi, Yoichiro; Murakami, Akiko; Kobayashi, Isao; Nara, Takeshi; Hashimoto, Muneaki; Kato, Motoyasu; Hidayat, Moulid; Suina, Kentaro; et al.
Abstract: Background: Zinc‐finger E‐box‐binding homeobox 1 (ZEB1) is an important regulator of epithelial‐mesenchymal transition (EMT) and is involved in the maintenance of cancer stem cells (CSCs) via miR‐200c and BMI1 pathway. Recent studies revealed that ZEB1 contributes to the EMT‐mediated acquired resistance to gefitinib in EGFR ‐mutant non‐small cell lung cancer (NSCLC). However, the precise role of ZEB1 in the maintenance of lung CSCs that lead to acquired resistance to gefitinib remains unclear. Methods: PC9 and HCC827 NSCLC cell lines were treated with high concentrations of gefitinib, and surviving cells were referred to as "gefitinib‐resistant persisters" (GRPs). ZEB1 knockdown or overexpression was performed to determine the biological significance of ZEB1 in the CSC features of GRPs, and animal models were studied for in vivo validation. Expression of ZEB1, BMI1, and ALDH1A1 was analyzed by immunohistochemistry in tumor specimens from NSCLC patients with acquired resistance to gefitinib. Results: GRPs had characteristic features of mesenchymal and CSC phenotypes with high expression of ZEB1 and BMI1, and decreased miR‐200c, in vitro and in vivo. ZEB1 silencing attenuated the suppression of miR‐200c, resulting in the reduction in BMI1 and reversed the mesenchymal and CSC features of GRPs. Furthermore, ZEB1 overexpression induced EMT and increased the levels of CD133‐ and BMI1‐positive GRPs in vitro and gefitinib resistance in vivo. Finally, ZEB1, BMI1, and ALDH1A1 were highly expressed in tumor specimens from EGFR ‐mutant NSCLC patients with gefitinib resistance. Conclusions: ZEB1 plays an important role in gefitinib‐resistant lung CSCs with EMT features via regulation of miR‐200c and BMI1. Abstract : Gefitinib‐resistant persisters (GRPs) of EGFR ‐mutant NSCLC cells have characteristic features of mesenchymal and CSC phenotypes. ZEB1 is highly expressed in GRPs and involved in the maintenance of lung CSCs resistant to gefitinib via miR‐200c‐BMI1 pathway.